2006
DOI: 10.1590/s0103-97332006000600049
|View full text |Cite
|
Sign up to set email alerts
|

Electrical and morphological properties of low resistivity Mo thin films prepared by magnetron sputtering

Abstract: Mo thin films have been deposited using a DC magnetron sputtering system with an S-gun configuration electrode and characterized electrically and morphologically. The influence of the sputtering gas pressure and glow discharge (GD) power, on the electrical resistivity of Mo thin films and on the contact resistivity of Mo to Cu(In,Ga)Se 2 (CIGS) films was determined through an exhaustive parameter study. This study also allowed us to find the conditions to deposit Mo films with suitable properties for its use a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
27
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(34 citation statements)
references
References 11 publications
6
27
0
1
Order By: Relevance
“…For a given deposition pressure the Mo film resistivity reduces as power increases in agreement with other reports [20][21][22]. …”
Section: Mo Growth and Na Diffusionsupporting
confidence: 92%
“…For a given deposition pressure the Mo film resistivity reduces as power increases in agreement with other reports [20][21][22]. …”
Section: Mo Growth and Na Diffusionsupporting
confidence: 92%
“…El sistema con la estructura Mo/CIS/Zn(O,OH)S/ZnO fue construido utilizando el siguiente procedimiento: como contacto eléctrico inferior de la celda se utilizó una película de Mo con un espesor de 1.1 µm; esta capa fue sintetizada utilizando un sistema de sputtering magnetrón DC con una configuración de electrodo tipo S-gun [8]. La capa absorbente CIS con 1 µm de espesor fue sintetizada por medio de coevaporación de In y Cu en una atmósfera de S utilizando un proceso de tres etapas [9].…”
Section: Methodsunclassified
“…Mo also emerged as the dominant choice for back contact layer of CuInSe 2 (CIS) and its gallium alloys (CIGS)-based solar cells because of its relative stability at the processing temperature, resistance to alloying with Cu and In, and its low contact resistance to CIS [7,8,6,1,3]. As the quality of the CIS film, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, low Argon mass-flow rates can reduce micropores and increase optical reflectance. Gordillo et al [3] deposited Mo thin films using a DC magnetron sputtering system with S-gun configuration electrode. They showed that it is possible to get low resistivity Mo films by decreasing the Argon partial pressure and increasing the power of the glow discharge.…”
Section: Introductionmentioning
confidence: 99%